The song that sings us - Davies, Nicola 1958- (Firefly Press, 2023)
When animals talk, it's time humans listened: Harlon has been raised to protect her younger siblings, twins Ash and Xeno, and their outlawed power of communicating with animals. But when the sinister Automators attack their mountain home they must flee for their lives. Xeno is kidnapped and Harlon and Ash are separated. In a thrilling and dangerous adventure they must all journey alone through the ice fields, forests and oceans of Rumyc to try to rescue each other and fulfil a mysterious promise about a lost island made to their mother
First published in 2021
Keywords: Fiction 13+; Children's / Teenage fiction & true stories; Teenage Fiction; Fantasy and Magic; Fantasy fiction; Young adult fiction; Jugendbuch